Exchange rate dynamics and regional trade integration in the WAMZ - Olorunsola E. Olowofeso; Maimuna John-Sowe; Santigie M. Kargbo; Adegoke I. Adeleke; Joseph R. Yengbe; Yaya Cham (West African Monetary Institute (WAMI), 2022)
This study examines the effects of bilateral exchange rate on trade flows in the WAMZ and assesses the role of complementarity trade structures in enhancing intra-WAMZ trade. The modified gravity model is used to assess whether efforts by WAMZ countries to facilitate transactions in national currencies and promote complementarity trade structures can enhance intra-WAMZ trade. The results from Poisson pseudo-maximum-likelihood (PPML)indicates some interesting results. It shows that there is positive and significant relationship between bilateral real exchange rate and bilateral exports, which suggests that a real depreciation of the exporting country's currency relative to the importing country's currency will stimulate bilateral exports. This clearly suggest that efforts by WAMZ countries to promote quoting and trading in national currencies will have a positive effect on bilateral trade flows among Member States. This relationship remains consistent despite controlling for endogeneity bias and using different alternative measurements for the key variables of interest. The estimated results also reveal that the extent of trade complementarity increases trade flows among WAMZ countries. Similarly, our findings for some other explanatory variables especially economic size indicates large elasticity of trade with respect to economic size. Suggesting that the economic size matters in promoting trade flows among WAMZ countries. Based on these findings this study recommends that WAMZ Member States should support efforts of the private sector to create the enabling infrastructure to support quoting and trading in national currencies. By encouraging cross-border trade and other transactions in national currencies, WAMZ countries can potentially avert large swings in exchange rates. These should be complemented by measures that will enhance trade complementarity structures, including encouraging regional value chains through trading in intermediate inputs across countries to enable WAMZ Member States to take advantage of the African Continental Free Trade Area (AfCFTA) initiative.
Keywords: F0; F15; F31; C23; 330; Exchange Rate; Trade Integration; Complementarity; Trade Structures; Gravity Model; WAMZ